2019
DOI: 10.3390/f10111022
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Mountain Tourism in a Traditional Forest Area of Greece

Abstract: The recreational value of forests in mountain areas creates significant potential for local growth. Indeed, in recent decades, it has been noted that there has been an increase in the popularity of forests recognized as tourism destinations with a strong recreational importance. In the forest area of Metsovo, the locals are aware of the role of tourism in local growth, and it is considered, along with forestry and livestock farming, as the major critical advantage for sustainable development. Research Highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…There is something indisputably tranquil about going out right into the wild and also checking out the range of mountains in the Malaysia, whether you're seeing the fog-covered Excellent Smoky Hills or the sharp, snowy optimal of the Alaska Array (Tampakis, Andrea, Karanikola & Pailas, 2019). We have actually rounded up 13 breathtaking Malaysia mountain ranges that have excellent walking as well as even far better views for your following journey into the outdoors.…”
Section: Background Of the Studymentioning
confidence: 99%
“…There is something indisputably tranquil about going out right into the wild and also checking out the range of mountains in the Malaysia, whether you're seeing the fog-covered Excellent Smoky Hills or the sharp, snowy optimal of the Alaska Array (Tampakis, Andrea, Karanikola & Pailas, 2019). We have actually rounded up 13 breathtaking Malaysia mountain ranges that have excellent walking as well as even far better views for your following journey into the outdoors.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Moreover, the ability to identify hidden effects and measure their impact on the safe operating space of multifunctionality is perhaps an important aspect when applying management strategies. Indeed, one can easily imagine that a direct effect of tree logging can affect the attractiveness of the forest, and eventually the functionality of tourism (Thorn et al, 2020;Mäntymaa et al, 2018Mäntymaa et al, , 2021Tampakis et al, 2019), yet an effect of tourism degradation sometimes can lead to a degradation of wood harvesting function. Our analysis has shown that in a governance medium of the forest, a negative effect on tourism can gravely affect the overall budget for infrastructure provision, which ultimately can lead to a lower functionality of wood harvesting.…”
Section: Interdependencies In Coupled Systemsmentioning
confidence: 99%
“…Recent research concludes that the existence of protected areas apart from the environmental scheme has also important impacts the socioeconomic status for the gateway communities [41]. Furthermore, the existing natural assets as well as the development of primary infrastructures for the facilitation of ecotourism growth are critical factors for improving of the residents' quality of life [42].…”
Section: The Awnp and Lmpastakeholders' Profilementioning
confidence: 99%